ANALISIS PERILAKU KONSUMTIF DAN PERILAKU MENABUNG MAHASISWA PENERIMA BEASISWA BIDIKMISI DI JURUSAN EKONOMI PEMBANGUNAN FAKULTAS EKONOMI UNIVERSITAS NEGERI MALANG ANGKATAN 2014 - Ahmad Abdur Rohman; Sri Umi Mintarti (Jurnal Pendidikan Ekonomi, 2018)
This study analyze consumptive behavior and saving behavior of students who receive bidikmisi scholarship. Some students allocate scholarship fund wisely for primary necessary, study necessary, and saving. But some students does consumptive behavior, as for travelling, buy branded clothes, and buy gadgets. The research method used is qualitative research with phenomenology approach. Sampling method used is snowball sampling. Data collection is done by observation, interview and documentation. Bidikmisi student’s consumptive behavior are divided into 2 class, there are low consumptive behavior and medium consumptive behavior. Bidikmisi students make consumption decision consider some factor as necessary, usefulness of good, quality, and budget. Bidikmisi student’s saving behavior done conditionally. Savings activities conducted every month depending on the amount of consumption.